Analysis of Erythrocyte Indices and Reticulocyte Hemoglobin Equivalent in Iron Deficiency Anemia on Treatment - Agnes Theresia Motulo; Rachmawati Muhiddin; Nadirah Rasyid Ridha; Mansyur Arif; Agus Alim Abdullah (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Assessment of treatment response is needed in the management of iron deficiency anemia (IDA). This study aims to analyze erythrocyte indices (MCH, MCV, MCHC) and Ret-He as indicators of IDA diagnosis and treatment response. A prospective cohort study in children ages 2-18 years old in orphanages throughout Makassar. Grouped into normal group and therapy group, consisting of IDA and iron deficiency groups. Elemental iron therapy 3mg/kg/day was given. Levels of MCV (fl), MCH (pg), MCHC (g/dL), and Ret-He (pg) were measured before and on the 8th day of therapy. The normality test of numerical variable data used the Kolmogorov-Smirnov test. The statistical test used the Mann-Whitney test, Wilcoxon Signed Rank test, and the Kruskal-Wallis test. Diagnostic value and cut-off determination using ROC curve analysis. Test results were significant if p<0.05. The sample consisted of 40 subjects each in both normal and therapy groups. The therapy group was divided into 7 IDA and 33 iron deficiency. ROC IDA curve on MCV obtained a cut-off of 76 fl, a sensitivity of 100%, a specificity of 95%, NPP of 77.8%, NPN of 100%, MCH obtained a cut-off of 25 pg, a sensitivity of 100%, 97.5% specificity of 97.5%, NPP of 87.5%, NPN of 100%, Ret-He obtained cut-off 29 pg, sensitivity of 100%, specificity of 95%, NPP of 77.5%, NPN of 100%. MCV levels increased by 7.3% (p<0.05) while Ret-He increased by 19.6% (p<0.05) after therapy. The ROC curve coordinate on IDA showed that cut-off levels of MCV 76 fl, MCH 25 pg, and Ret-He 29 pg provided optimal sensitivity and specificity. Increasing MCV after therapy described increasing levels in erythrocyte and hematocrit synthesis. Increasing Ret-He after therapy described improving erythropoiesis quality. MCV, MCH, and Ret-He as indicators of diagnosing IDA. MCV and Ret-He monitor the success of IDA treatment response.